Different outcomes for relapsed vs. refractory neuroblastoma after therapy with (131)I-metaiodobenzylguanidine ((131)I-MIBG) - Zhou, Margaret J. (Eur J Cancer, 2015)
BACKGROUND: (131)I-metaiodobenzylguanidine ((131)I-MIBG) is a targeted radiopharmaceutical with significant activity in high-risk relapsed and chemotherapy-refractory neuroblastoma. Our primary aim was to determine if there are differences in response rates to (131)I-MIBG between patients with relapsed and treatment-refractory neuroblastoma. METHODS: This was a retrospective cohort analysis of 218 patients with refractory or relapsed neuroblastoma treated with (131)I-MIBG at UCSF between 1996 and 2014. Results were obtained by chart review and database abstraction. Baseline characteristics and response rates between relapsed patients and refractory patients were compared using Fisher exact and Wilcoxon rank sum tests, and differences in overall survival (OS) were compared using the log-rank test. RESULTS: The response rate (complete and partial response) to (131)I-MIBG-based therapies for all patients was 27%. There was no difference in response rates between relapsed and refractory patients. However, after (131)I-MIBG, 24% of relapsed patients had progressive disease compared to only 9% of refractory patients, and 39% of relapsed patients had stable disease compared to 59% of refractory patients (p = 0.02). Among all patients, the 24-month OS was 47.0% (95% CI 39.9%–53.9%). The 24-month OS for refractory patients was significantly higher at 65.3% (95% CI 51.8%–75.9%), compared to 38.7% (95% CI 30.4%–46.8%) for relapsed patients (p < 0.001). CONCLUSIONS: Although there was no significant difference in overall response rates to (131)I-MIBG between patients with relapsed vs. refractory neuroblastoma, patients with prior relapse had higher rates of progressive disease and had lower 2-year overall survival after (131)I-MIBG compared to patients with refractory disease.